Cloning, purification, kinetic and anion inhibition studies of a recombinant β-carbonic anhydrase from the Atlantic salmon parasite platyhelminth Gyrodactylus salaris. (31st December 2022) - Aspatwar, Ashok; Barker, Harlan; Aisala, Heidi; Zueva, Ksenia; Kuuslahti, Marianne; Tolvanen, Martti; Primmer, Craig R.; Lumme, Jaakko; Bonardi, Alessandro; Tripathi, Amit; Parkkila, Seppo; Supuran, Claudiu T.
Abstract: A β-class carbonic anhydrase (CA, EC 4.2.1.1) was cloned from the genome of the Monogenean platyhelminth Gyrodactylus salaris, a parasite of Atlantic salmon. The new enzyme, GsaCAβ has a significant catalytic activity for the physiological reaction, CO2 + H2 O ⇋ HCO3 − + H + with a kcat of 1.1 × 10 5 s −1 and a kcat /Km of 7.58 × 10 6 M −1 × s −1 . This activity was inhibited by acetazolamide (KI of 0.46 µM), a sulphonamide in clinical use, as well as by selected inorganic anions and small molecules. Most tested anions inhibited GsaCAβ at millimolar concentrations, but sulfamide (KI of 81 µM), N, N -diethyldithiocarbamate (KI of 67 µM) and sulphamic acid (KI of 6.2 µM) showed a rather efficient inhibitory action. There are currently very few non-toxic agents effective in combating this parasite. GsaCAβ is subsequently proposed as a new drug target for which effective inhibitors can be designed.